2018
DOI: 10.1038/s41467-018-06114-3
|View full text |Cite
|
Sign up to set email alerts
|

SNX3-retromer requires an evolutionary conserved MON2:DOPEY2:ATP9A complex to mediate Wntless sorting and Wnt secretion

Abstract: Wntless transports Wnt morphogens to the cell surface and is required for Wnt secretion and morphogenic gradients formation. Recycling of endocytosed Wntless requires the sorting nexin-3 (SNX3)-retromer-dependent endosome-to-Golgi transport pathway. Here we demonstrate the essential role of SNX3-retromer assembly for Wntless transport and report that SNX3 associates with an evolutionary conserved endosome-associated membrane re-modelling complex composed of MON2, DOPEY2 and the putative aminophospholipid trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 79 publications
0
63
1
Order By: Relevance
“…At a superficial level, the mammalian heterodimers of SNX1 (or SNX2) with SNX5 (or SNX6) are localised to endosomal structures that generally co‐localise with the core Retromer trimer by confocal fluorescence microscopy, and an interaction between mammalian Retromer and the SNX‐BAR proteins has been observed using yeast two hybrid assays and co‐immunoprecipitation . In contrast, super‐resolved stimulated emission depletion (STED) microscopy suggested that Vps35 and SNX1 occupy distinct domains on the endosome, and the interaction of Retromer with the SNX‐BAR proteins appears to be very weak compared to other known ligands such as SNX3 and SNX27 . Several recent studies have brought this link between Retromer and SNX‐BAR proteins in higher eukaryotes into sharper focus .…”
Section: The Retromer and Snx‐bar Controversymentioning
confidence: 99%
See 2 more Smart Citations
“…At a superficial level, the mammalian heterodimers of SNX1 (or SNX2) with SNX5 (or SNX6) are localised to endosomal structures that generally co‐localise with the core Retromer trimer by confocal fluorescence microscopy, and an interaction between mammalian Retromer and the SNX‐BAR proteins has been observed using yeast two hybrid assays and co‐immunoprecipitation . In contrast, super‐resolved stimulated emission depletion (STED) microscopy suggested that Vps35 and SNX1 occupy distinct domains on the endosome, and the interaction of Retromer with the SNX‐BAR proteins appears to be very weak compared to other known ligands such as SNX3 and SNX27 . Several recent studies have brought this link between Retromer and SNX‐BAR proteins in higher eukaryotes into sharper focus .…”
Section: The Retromer and Snx‐bar Controversymentioning
confidence: 99%
“…Together with Rab7, SNX3 is important for the stable recruitment and activity of Retromer on endosomal membranes . SNX3‐Retromer is involved in the retrograde transport of cargo receptors including the Wnt sorting receptor Wntless, transferrin receptor, the divalent metal ion transporter Dmt1‐II, and CI‐MPR, in carriers that are morphologically and functionally distinct from the SNX‐BAR proteins in higher eukaryotes . It has also been suggested that the SNX3 homologue SNX12 can perform a similar role .…”
Section: Snx Proteins As Retromer Cargo Adaptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This included AP-1 adaptors (AP1G1, AP1S2, AP1AR, AP1M1 and AP1S1) and accessory proteins (CLINT1, SYNRG, PI4K2B and Rab9), but not their associated clathrin coat (15,17,24,25). We also found proteins involved in retromer-dependent transport (SNX3, SNX4, VPS35, VPS26, VPS29), along with SNX-BAR proteins potentially involved in retromer-independent transport (SNX1, SNX2, SNX5 and SNX6) (26)(27)(28). Many peripheral membrane proteins are localised to multiple compartments in the cell, making them difficult to classify by spatial proteomics (Fig.…”
Section: Adaptor Proteins and Accessory Factors Of Vesicles Specific mentioning
confidence: 83%
“…When Wnt is present in the cytoplasm, (Fig. 1B), it will be lipidated by a special palmitoyl transferase-porcupine [34], further modified by Wntless in the Golgi and finally secreted by exocytosis [35,36]. Frizzled (FZD) receptors, the principal receptors for Wnts, consist of seven-transmembrane proteins and cysteine-rich domain (CRD) in the N-terminal [37,38].…”
Section: Canonical Wnt Pathway Activation Mechanismmentioning
confidence: 99%